these are my four options,

I just dont know which one it is, can you also possibly explain it?

Thank you

Guest May 21, 2017

#1**+1 **

x^4 - 3x^3 - x^2 - 27x - 90 = 0

It's not easily factored, but let's guess, initially, that either 2, or -2 is one of the roots

Let's check - 2, first

(-2)^4 - 3(-2)^3 - (-2)^2 - 27(-2) - 90 =

16 + 24 - 4 + 54 - 90 =

94 - 94 = 0

So......-2 is a root

Two answers include -2, but one of them has only 5 as the other possible root....then the possible factorization of the polynomial is either :

(x + 2)^2 ( x - 5)^2 but the ending constant will = 100 so this is no good

(x + 2)^3 (x - 5) but the ending constant = -40....no good either

(x +2) (x - 5)^3 but the ending constant is -250.....nope

So.......the only possible solution is 5, -2, 3i, -3i

Check

(x - 5) (x + 2) (x - 3i) (x + 3i) =

( x^2 - 3x -10) ( x^2 - 9i^2) =

(x^2 - 3x -10) (x^2 + 9) =

x^4 + 9x^2 - 3x^3 - 27x - 10x^2 - 90 =

x^4 - 3x^3 - x^2 - 27x - 90 !!!!

CPhill
May 21, 2017

#3**+1 **

B; The solutions are 5, -2, 3i, and -3i

Let's look at the original equation:

\(x^4-3x^3-x^2-27x-90=0\)

Our goal is to get the left hand side into parts that are more manageable to work with. I'll try to explain this. We'll use the rational root theorem. This says that if a polynomial equation can be written in the form \(a_nx^n+a_{n-1}x^{n-1}+...+a_0\) and if \(a_0\) and \(a_n\) are integers, then the factor can be found by checking numbers produced by doing \(\pm\frac{dividers\hspace{1mm}of\hspace{1mm}a_0}{dividers\hspace{1mm}of\hspace{1mm}a_n}\).

Dividers of \(a_0:\hspace{1mm}1,2,3,5,6,9,10,15,18,30,45,90\)

Dividers of \(a_n:\hspace{1mm}1\)

Therefore, check for one rational solution by doing: \( \pm\frac{1,2,3,5,6,9,10,15,18,30,45,90}{1}\)

-2 happens to be the first value that satisfies this equation. The opposite of that is 2, so a factor is x+2.

\(\frac{x^4-3x^3-x^2-27x-90}{x+2}=x^3-5x^2+9x-45\), so the monstrosity we had before goes to \((x+2)(x^3-5x+9x-45)=0\).

Thankfully, this is the hardest part. Now, we have to factor \((x^3-5x^2+9x-45)\) further. Find another factor by grouping:

\((x^3-5x^2)+(9x-45)\)

Factor out an x^2 from the first set of parentheses and 9 from the second set and then factor the resulting common term, which happens to be (x-5):

\((x^3-5x^2)+(9x-45)=x^2(x-5)+9(x-5)=(x^2+9)(x-5)\)

After all this effort, we have transformed \(x^4-3x^3-x^2-27x-90\) to \((x+2)(x-5)(x^2+9)\).

Okay, now use the zero factor principle. In other words, set each factor to zero:

\(x+2=0\hspace{1cm}x-5=0\hspace{1cm}x^2+9=0\)

Let's focus on the easy ones first:

\(x=-2 \) and \(x=5\).

Now the harder factor:

\(x^2+9=0\)

\(x^2=-9\)

\(x=\pm\sqrt{-9}\)

\(x=\pm3i\)

Solution set is 5,2,3i, -3i

TheXSquaredFactor
May 21, 2017